Harvest prediction and control in interspecific hybrid Elaeis oleifera x Elaeis guineensis at Colombian west area of palm production. I. Ripeness period determination in order to obtain high amounts of oil concentration at bunches - Preciado Q., Cindy Amelia; Bastidas P., Silvio; Betancourth Garcia, Carlos Arturo; Peña R., Eduardo; Reyes Chávez, Rafael (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
This study was carried out to identify the ripeness period in order to obtain high amounts of oil concentration in bunches of the OxG hybrid (Elaeis oleifera x Elaeis guineensis) Corpoica Elmira in the palm production region of Tumaco, Colombia. The highest period of oil concentration in bunches was obtained between 170 and 180 days after assisted pollination, within this range it's possible to harvest the largest number of bunches with fruit at optimum ripeness. Variables such as oil to dry mesocarp ratio of fertile fruits (AcPSFF), oil to dry mesocarp ratio of parthenocarpic fruits (AcPSFP), oil to wet mesocarp ratio of parthenocarpic fruit (AcPFFP), oil to bunch ratio based on parthenocarpic fruit (AcRFP), and oil to bunch ratio (AcR), are sensitive to ripeness periods.